For this case we have the following expression:
[tex]12-2x-3y^5[/tex]
If [tex]x = 2[/tex]
[tex]y = -4[/tex]
We substitute the values in the given expression:
[tex]12-2 (2) -3 (-4) ^ 5 =[/tex]
We solve the operations that are inside the parentheses:
Applying law of power and law of signs we have:
[tex]12-4-3 ((- 4) (- 4) (- 4) (- 4) (- 4)) =[/tex]
Simplifying the operation within parentheses:
[tex]12-4-3 (-1024) =[/tex]
Multiplying:
[tex]12-4 + 3072 =[/tex]
Adding algebraically we have:
[tex]12-4 + 3072 = 3080[/tex]
Answer:
The value of [tex]12-2x-3y^5[/tex] for [tex]x = 2[/tex] and[tex]y = -4[/tex] is 3080.